INVESTIGATING THE SIGNIFICANCE OF THE REFLECTION STAGE IN MICROTEACHING AT THE SIXTH SEMESTER OF STUDENT AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Riska Amalia; Nunung Anugrawati; Farisha Andi Baso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research aimed to find out the significance of the reflection as one of stage when implementing microteaching practices. The subjects in this research were sixth semester students at Universitas Muhammadiyah Makassar who were selected using purposive sampling technique. This method of research was qualitative research with phenomena experienced by the subject of research. This research data was collected through semi-structured interview. Data analysis technique used data minimization, data visualization, and conclusion or interpretation. The results of this research showed that the reflection stage in microteaching was very important and beneficial to do because it could help students and teachers in evaluating and improving the quality of education. Therefore, it is important for educational institutions to continue to encourage and facilitate consistent and in-depth reflection practices, so that students can fully benefit from this process and achieve optimal academic and personal potential.